2009
DOI: 10.1182/blood-2008-08-173963
|View full text |Cite
|
Sign up to set email alerts
|

Identification and molecular characterization of recurrent genomic deletions on 7p12 in the IKZF1 gene in a large cohort of BCR-ABL1–positive acute lymphoblastic leukemia patients: on behalf of Gruppo Italiano Malattie Ematologiche dell'Adulto Acute Leukemia Working Party (GIMEMA AL WP)

Abstract: The BCR-ABL1 fusion gene defines the subgroup of acute lymphoblastic leukemia (ALL) with the worst clinical prognosis. To identify oncogenic lesions that combine with BCR-ABL1 to cause ALL, we used Affymetrix Genome-Wide Human SNP arrays (250K NspI and SNP 6.0), fluorescence in situ hybridization, and genomic polymerase chain reaction to study 106 cases of adult BCR-ABL1-positive ALL. The most frequent somatic copy number alteration was a focal deletion on 7p12 of IKZF1, which encodes the transcription factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
172
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(184 citation statements)
references
References 26 publications
(34 reference statements)
7
172
0
2
Order By: Relevance
“…Although deletions targeting IKZF1 were shown to be present at high frequencies in ALL, these defects have not yet been observed in de novo AML, 31 or in other myeloid disorders. Our results show that deletions of IKZF1 occur in 21% of post-MPN AML patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although deletions targeting IKZF1 were shown to be present at high frequencies in ALL, these defects have not yet been observed in de novo AML, 31 or in other myeloid disorders. Our results show that deletions of IKZF1 occur in 21% of post-MPN AML patients.…”
Section: Discussionmentioning
confidence: 99%
“…40,41 However, single-nucleotide polymorphism array profiling studies of both ALL and chronic myeloid leukemia have shown that expression of these dominant-negative transcripts is determined by the presence of IKZF1 deletions that involve the exons corresponding to those deleted in the aberrant IKZF1 transcripts and IKZF1 protein. 20,30 Alterations in IKAROS function have an important role in the pathogenesis of lymphoid tumors. Mice harboring a dominantnegative mutation in the Ikzf1 gene develop an aggressive T-lineage lymphoproliferative disease.…”
Section: Genomic Profiling Of High-risk Allfa Central Role Of Ikzf1mentioning
confidence: 99%
“…15,28 In contrast, ETV6-RUNX1 and BCR-ABL1 (Ph þ ) ALL cases harbor multiple distinct copy number alterations. 15,29 Deletion of IKZF1 (IKAROS) is a hallmark of Ph þ lymphoid leukemia, including both childhood and adult de novo ALL cases 20,30 and chronic myeloid leukemia at progression to lymphoid blast crisis 20,30 (Table 1). Moreover, the presence of IKZF1 alterations is associated with poor outcome in Ph þ ALL.…”
Section: Genomic Profiling Of High-risk Allfa Central Role Of Ikzf1mentioning
confidence: 99%
“…IKZF1 encodes for a transcription factor, which is an important regulator of lymphoid cell differentiation. Subsequently, the complete cohort of 39 BC-CML cases, including the three patients with an IKZF1 deletion already detected by cytogenetic arrays, was investigated or confirmed for IKZF1 deletions by PCR using specific primer pairs for the common intragenic deletions spanning from exon 2 to 7 or from exon 4 to 7, as published by Iacobucci et al 6 In total, in 17.9% (7/39) of all cases intragenic IKZF1 deletions were observed (1/7 exon D2-7; 6/7 exon D4-7).…”
mentioning
confidence: 99%